Employers’ experience of employees with cancer: trajectories of complex communication - Tiedtke, C. M. (J Cancer Surviv, 2017)
PURPOSE: Remaining in paid work is of great importance for cancer survivors, and employers play a crucial role in achieving this. Return to work (RTW) is best seen as a process. This study aims to provide insight into (1) Dutch employers’ experiences with RTW of employees with cancer and (2) the employers’ needs for support regarding this process. METHODS: Thirty employer representatives of medium and large for-profit and non-profit organizations were interviewed to investigate their experiences and needs in relation to employees with cancer. A Grounded Theory approach was used. RESULTS: We revealed a trajectory of complex communication and decision-making during different stages, from the moment the employee disclosed that they had been diagnosed to the period after RTW, permanent disability, or the employee’s passing away. Employers found this process demanding due to various dilemmas. Dealing with an unfavorable diagnosis and balancing both the employer’s and the employee’s interests were found to be challenging. Two types of approach to support RTW of employees with cancer were distinguished: (1) a business-oriented approach and (2) a care-oriented approach. Differences in approach were related to differences in organizational structure and employer and employee characteristics. Employers expressed a need for communication skills, information, and decision-making skills to support employees with cancer. CONCLUSIONS: The employers interviewed stated that dealing with an employee with cancer is demanding and that the extensive Dutch legislation on RTW did not offer all the support needed. We recommend providing them with easily accessible information on communication and leadership training to better support employees with cancer. IMPLICATIONS FOR CANCER SURVIVORS: • Supporting employers by training communication and decision-making skills and providing information on cancer will contribute to improving RTW support for employees with cancer. • Knowing that the employer will usually be empathic when an employee reveals that they have been diagnosed with cancer, and that the employer also experiences difficulties and dilemmas, might lower the threshold to discuss wishes regarding disclosure, communication, and work issues. • The interests of employer and employee in relation to RTW are interrelated; both have responsibility and a role to play, and are in need of support.